¡Turismo para veganos! Diversificación de la oferta turística para la satisfacción de un segmento emergente en Bogotá, Colombia. (2021)
This research was carried out with the purpose of recognizing the types of tourism that can be adapted to satisfy the needs of the vegan segment in the city of Bogota to enjoy their free time in order to develop tourism protocols that can be implemented in such activities. An analytical study was carried out at an apprehensive level. The population sample was composed of 260 vegans from the city of Bogotá who like to travel, to whom a self-directed virtual survey was sent through social networks such as Facebook and Instagram. The results obtained showed that there is no preference or inclination for any specific type or tourist activity; in fact, tastes and preferences are diverse. The only purpose of a vegan tourist is not to harm the lives of non-human animals. This is a study that lays the groundwork for future research related to tourism and veganism.